ASR, Volume 17, n° 1, 2013 - Full Issue - Journal System, (African Sociological Review, 2014)
Contents Editorial ...................................................1 General Issues Negation and Affirmation: a critique of sociology in South Africa Bongani Nyoka ....................................................2 Research Papers Perceived Threat of Malaria and the Use of Insecticide Treated Bed Nets in Nigeria Ali Arazeem Abdulahi, Cecilia Van Zyl-Schalekamp & Anton Senaka ...............................25 Women and Development in Urban Senegal: Microcredit and Social Capital Safiétou Kane ...................................................45 Provider expectations and father involvement: learning from experiences of poor “absent fathers” in Gauteng, South Africa Eddy Mazembo Mavungu ............................................65 Trust Creation in the Informal Economy: The Case of Plastic Bag Sellers of Mwanza, Tanzania Dominic Burbidge ..........................................................79 Éducation relative à l’environnement et médecine traditionnelle : cas des femmes déplacées internes de la crise postélectorale de 2010 en Côte d’Ivoire Kabran Aristide Djane .........................................................104 Essay Nietzsche l’islam et la globalisation Sanekli Monia ...............................................122 Book Review Define and Rule: Native as Political Identity, Mahmood Mamdani. Lwazi Siyabonga Lushaba ..........................................139